2006
DOI: 10.4269/ajtmh.2006.74.198
|View full text |Cite
|
Sign up to set email alerts
|

Point Mutations in the Dihydrofolate Reductase and Dihydropteroate Synthase Genes of Plasmodium Falciparum and Resistance to Sulfadoxine-Pyrimethamine in Sri Lanka

Abstract: Sulfadoxine-pyrimethamine (SP) is the second-line treatment for Plasmodium falciparum malaria in Sri Lanka. Resistance to SP is caused by point mutations in the dihydrofolate reductase (Pf-dhfr) and dihydropteroate synthase (Pf-dhps) genes of P. falciparum. We determined the genotype of Pf-dhfr and Pf-dhps and the clinical response to SP in 30 field isolates of P. falciparum from Sri Lanka. All patients treated with SP had an adequate clinical response. Eighty-five percent (23 of 27) of pure field isolates car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
7
6
0
Order By: Relevance
“…Nevertheless, with no clear reason, a sharp increase was observed in N 51 R 59 N 108 I 164 /S 436 G 437 haplotype from 2010 to 2014, which is the same as what was reported from Northeastern India (Mishra et al, 2014). The predominant pfdhfr haplotype in Iran seems to be N51,59R,108N rather than 51I,59R,108N similar to the previous reports from Afghanistan (Awab et al, 2013), Pakistan (Khatoon et al, 2009;Ghanchi et al, 2011;Kolaczinski et al, 2012), India (Biswas et al, 2000;Ahmed et al, 2004;Garg et al, 2009), Sri Lanka (Hapuarachchi et al, 2006), and Papua New Guinea (Mita et al, 2006). Therefore, mutation 51I might be a good molecular marker for rapid detection of triple mutant, showing pyrimethamine failure in Iran and its neighboring countries, Afghanistan and Pakistan.…”
Section: Discussionsupporting
confidence: 89%
“…Nevertheless, with no clear reason, a sharp increase was observed in N 51 R 59 N 108 I 164 /S 436 G 437 haplotype from 2010 to 2014, which is the same as what was reported from Northeastern India (Mishra et al, 2014). The predominant pfdhfr haplotype in Iran seems to be N51,59R,108N rather than 51I,59R,108N similar to the previous reports from Afghanistan (Awab et al, 2013), Pakistan (Khatoon et al, 2009;Ghanchi et al, 2011;Kolaczinski et al, 2012), India (Biswas et al, 2000;Ahmed et al, 2004;Garg et al, 2009), Sri Lanka (Hapuarachchi et al, 2006), and Papua New Guinea (Mita et al, 2006). Therefore, mutation 51I might be a good molecular marker for rapid detection of triple mutant, showing pyrimethamine failure in Iran and its neighboring countries, Afghanistan and Pakistan.…”
Section: Discussionsupporting
confidence: 89%
“…The triple mutant 51 I 59 R 108 N (24,8%) was of low prevalence in the examined isolates, similarly to previous data reported in Sri Lanka [42] and Papua New Guinea [43], but different from the isolates from Malaysia [44], Brazil [45] and India [46] where this triple mutant was the predominant haplotype. In Africa, the Republic of Congo [28] and Gabon [29] also shows differences when compared with these Angolan data, except in the province of Cabinda.…”
Section: Discussionsupporting
confidence: 87%
“…The results for dhps , in contrast to dhfr , revealed a greater proportion of wildtype alleles in the population. Similar data have been noted in previous studies, and Nzila et al [40] have suggested that after the triple mutant dhfr alleles spread sufficiently through a population, dhps mutant alleles increase in frequency due to selection by sulphadoxine [14,40,41]. While dhfr double mutants were predominantly present, triple mutants increased in frequency from 1992-1999, in accordance with positive selection for those mutants.…”
Section: Discussionsupporting
confidence: 87%